Developing Digital Examination System Security through the Implementation of the RC4 Algorithm - Lubis, Muhammad Luthfi Moratuah; Rahmad, Iwan Fitrianto (Jurnal ICT : Information and Communication Technologies, 2025)
The increasing shift toward digital-based academic administration presents significant challenges for educational institutions, particularly regarding the security of examination data, which remains vulnerable when managed through manual processes. To address this issue, this study aims to develop and implement a secure web-based digital examination system using the RC4 cryptographic algorithm to ensure the confidentiality, integrity, and availability of assessment records at Harapan Mekar 1 Vocational School. Employing the CRISP-DM methodology, the research includes business understanding, data preparation, system development, encryption–decryption integration, and system validation. The RC4 algorithm, known for its lightweight structure and fast computational performance, was applied to encrypt student, teacher, and examination data across all operational modules. The results show that the system successfully encrypts and decrypts data through stable implementation of the Key Scheduling Algorithm (KSA) and Pseudo Random Generation Algorithm (PRGA), thereby strengthening protection against unauthorized access and eliminating risks associated with traditional manual data handling. The system effectively enhances operational efficiency and data security, demonstrating that RC4 remains a viable encryption option for educational environments with limited computational resources. This study offers practical implications for schools seeking accessible security solutions and serves as a reference for further system enhancements using more advanced cryptographic algorithms or extended digital examination features.